Effects of Punica Granatum Seed Hydromethanol Extract on Contractility of Isolated Aorta in Female Albino Rats - Al-Habib, Omar A. M.; Adam, Lina N. (Science Journal of University of Zakho, 2017)
The aim of the present study was to evaluate the physiological effect of the Punica granatum hydromethanol seeds extract on the contractility of isolated rat aortic rings. The isolated rat’s thoracic aorta was placed in an organ bath containing Krebs solution and the contraction was recorded isometrically. The results demonstrated that P. granatum hydro- methanol extract (1.5 to 5 mg/ml) caused a significant relaxant effect on the contractions induced by phenylephrine (0.01 mM) with IC50 ± SEM of 2.682 ± 0.197 mg/ml and the percentage of relaxation for PE-induced contraction was 52.88 ± 0.831. In endothelium intact and denuded aortic rings, the extract induced more or less the same response, except at high concentrations used (4.5 – 5.0 mg/ml) in which the endothelium denuded rings produced a significant reduction in the percent of relaxation from 49.91 to 25.42. Relaxant effect of hydromethanol seed extracts on intact aorta was not affected by nitric oxide synthase sinhsibitor ( L-NAME, 3*10-4), gaunyl cyclase inhibitor ( methylene blue 1*10-5) and PGI2 inhibitor (Indomethacin, 3*10-5), and thus, the percentages of relaxation were 59.85 ± 0.084, 58.59 ± 0.566 and 56.76 ± 0.693 respectively. In addition, incubation of aortic rings with the K+ channels blockers TEA, GLIB, 4AP and BaCl2, that Kca, KATP and Kv channels played no role on vasorelaxation induced by hydromethanol extract, while Kir enhanced the relaxation induced by the extract to76.40%. Finally, hydro methanol extract significantly enhanced dose-response relaxation after incubation of thoracic aortic rings with Nifedipine (10-6 M) to 91.91 % with IC50 ± SEM 1.774 ± 0.096. It can be concluded from the results of the current work that the fraction of Punica granatum hydromethanol seed extract has vasorelaxant effects on rat aortic which was partially dependent on endothelium, Kir and Ca channels.